Visual loss in urban and rural chronic glaucoma patients in Ghana - Ntim-Amponsah, C.T. (Tropical Doctor, 2002)
The visual acuity of newly diagnosed glaucoma patients in a rural and an urban area were compared in a hospital-based cross-sectional study in Ghana. Age at presentation was strikingly higher in the rural group due to local factors which result in a difference-in-age structure of the rural and urban population. The crude relative frequency of bilateral blindness was significantly higher for rural than urban. However, with age adjusted relative frequencies for bilateral blindness there was no significant difference between rural and urban patients. There was significant difference between them for those aged 51–71 when blindness in one or both eyes were considered together. There was more consistent blindness in the rural community: the difference was attributed to local factors such as better access to eye care in the urban group. © 2002, SAGE Publications. All rights reserved.